A global review of operational fishery interactions with killer whales (Orcinus orca): dynamics, impacts, and management strategies - Emma Luck; Hannah Myers; Keith R. Criddle (Frontiers in Marine Science, 2025)
Killer whales ( Orcinus orca ) are cosmopolitan, apex predators that sometimes interact with commercial fisheries. These fishery interactions can affect killer whales, sometimes harmfully, and cause negative socioeconomic consequences for the fishing industry. This review examines global trends in commercial fishery interactions with killer whales by analyzing 69 articles published between 1963 and 2024. These articles noted interactions between killer whales and fisheries in all oceans, but especially at high latitudes. Most documented interactions involved the depredation of longlines. Killer whales have been observed depredating a minimum of 30 species, mainly large fish such as tunas ( Thunnus spp.). Bycatch, injuries, fishers’ retaliatory measures, and artificial provisioning impacted killer whales that interacted with fisheries. Various mitigation measures have been tested with mixed success. This review outlines policy options to address interactions between killer whales and fisheries and identifies existing knowledge gaps.

First documented movement of wild killer whales ( Orcinus orca ) between Iceland and Norway - Marie‐Thérèse Mrusczok; Emma Luck; Ted Cheeseman; Jamie Coleman; Javier Cotín; Andrew Peacock; Robert A. Stefansson; Menja von Schmalensee (Marine Mammal Science, 2025)